PENGEMBANGAN PERANGKAT PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERINTEGRASI SCIENCE TECHNOLOGY ENGINEERING AND MATHEMATICS (STEM) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA PADA MATERI KIMIA HIJAU - Fitriawati, Ari; Sutoyo, Suyatno; Novita, Dian (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2026)
This research aims to develop Project-Based Learning (PjBL) learning tools integrated with Science, Technology, Engineering, and Mathematics (STEM) on Green Chemistry material that are valid, practical, and effective in improving high school students' creative thinking skills. The low creative thinking skills of Indonesian students as shown in the PISA 2022 report serves as the background for the urgency of this research. The development model used is the 4-D model (Define, Design, Develop, Disseminate) limited to the Develop stage. The products developed include lesson plans (RPP), student worksheets (LKPD), teaching materials, and assessment instruments. Validation was conducted by three expert validators, practicality testing through observation of learning implementation on 36 students, and effectiveness testing through pre-test and post-test on 72 grade X students at SMAN 1 Kedungadem Bojonegoro. The research results show that the learning tools meet valid criteria with Aiken Index ranging from 0.87–0.93 and reliability of 87.5%. The tools are also practical with learning implementation reaching 78.4% and student activities 81.2%. The paired sample t-test results show a significant increase in students' creative thinking skills from